Panchakarma Ayurveda in the Global Wellness Industry: A Critical Analysis of the Epistemological Transformation of Traditional Therapies - Ni Nyoman Siswati; Wayan Dharma Diantini; I Putu Eka Pradana; Kadek Oktarina Saridewi; Ankita Panchanan Singh (Yayasan Albahriah Jamiah Indonesia, 2026)
The expansion of the global wellness industry over the past two decades has driven the integration of traditional medicine systems into the transnational health market, including Ayurveda, with Panchakarma as its core therapy. While numerous studies have addressed the commercialization of traditional medicine, few have specifically examined the epistemological transformation of Panchakarma as it has been relocated within the logic of the global wellness industry. This study aims to analyze the changing knowledge frameworks, forms of practice, and therapeutic authority structures of Panchakarma amid globalization and to formulate its conceptual implications for the study of traditional medicine and health economics. The study employs a critical qualitative approach through a systematic review of scientific articles, policy documents, classical Ayurvedic texts, and promotional materials from international wellness centers from 2000–2025, analyzed using a critical discourse analysis framework based on Norman Fairclough’s perspective. The results show that Panchakarma has undergone an epistemological redefinition, moving from a holistic therapy based on tridosha cosmology and individual diagnosis to a standardized detoxification package fragmented into separate procedures such as oil massage, herbal steam, and cleansing therapy without a traditional diagnostic framework. The process of scientification and medicalization places these practices in biomedical terms—for example, detoxification, immunomodulation, and stress reduction—to gain scientific legitimacy, while simultaneously producing the commodification of knowledge and shifting authority from vaidyas to corporatized wellness institutions. This transformation emphasizes that the globalization of wellness is not simply expanding access but reconstructing therapeutic epistemologies through mechanisms of standardization, markets, and regimes of scientific truth, with important implications for the relations of knowledge, power, and economics within traditional healing practices.